Frequent alterations in p16/CDKN2A identified by immunohistochemistry and FISH in chordoma. (8th January 2020) - Cottone, Lucia; Eden, Nadia; Usher, Inga; Lombard, Patrick; Ye, Hongtao; Ligammari, Lorena; Lindsay, Daniel; Brandner, Sebastian; Pižem, Jože; Pillay, Nischalan; Tirabosco, Roberto; Amary, Fernanda; et al.
Abstract: The expression of p16 /CDKN2A, the second most commonly inactivated tumour suppressor gene in cancer, is lost in the majority of chordomas. However, the mechanism(s) leading to its inactivation and contribution to disease progression have only been partially addressed using small patient cohorts. We studied 384 chordoma samples from 320 patients by immunohistochemistry and found that p16 protein was lost in 53% of chordomas and was heterogeneously expressed in these tumours. To determine if CDKN2A copy number loss could explain the absence of p16 protein expression we performed fluorescence in situ hybridisation (FISH) for CDKN2A on consecutive tissue sections. CDKN2A copy number status was altered in 168 of 274 (61%) of samples and copy number loss was the most frequent alteration acquired during clinical disease progression. CDKN2A homozygous deletion was always associated with p16 protein loss but only accounted for 33% of the p16‐negative cases. The remaining immunonegative cases were associated with disomy (27%), monosomy (12%), heterozygous loss (20%) and copy number gain (7%) of CDKN2A, supporting the hypothesis that loss of protein expression might be achieved via epigenetic or post‐transcriptional regulatory mechanisms. We identified that mRNA levels were comparable in tumours with and without p16 protein expression, but other events including DNA promoter hypermethylation, copy number neutral loss of heterozygosity and expression of candidate microRNAs previously implicated in the regulation of CDKN2A expression were not identified to explain the protein loss. The data argue that p16 loss in chordoma is commonly caused by a post‐transcriptional regulatory mechanism that is yet to be defined.